MANAGERIAL ABILITY, MANAGEMENT COMPENSATION, BANKRUPTCY RISK, TAX AGGRESSIVENESS - Ridwan Nurfauzi; Amrie Firmansyah (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2018)
Manager with higher ability tends to have a deeper understanding of the firm’s strengths and weaknesses to take full advantage of opportunities, including an opportunity to do tax aggressiveness which is undetected by the tax authorities. In addition, the compensation received by management can also be a motivation for managers to act aggressively. Furthermore, the high risk of bankruptcy also puts pressure on managers to do cash tax saving aggresively in order to maintain the company's life.This study is aimed to examine the effect of managerial ability, management compensation and bankruptcy risk on tax aggressiveness. The sample used in this research are manufacturing companies listed on the Indonesia Stock Exchange (BEI) during the period of 2011 to 2015. Using purposive sampling, this research obtained data from 36 companies. So the total sample in this study amounts to 180 observation data.Managerial ability is measured by Data Envelopment Analysis (DEA) and Tobit regression referring to Park et al (2015). Management compensation is measured by the total compensation received by the director during the fiscal year (Armstrong, Blouin and Larcker, 2012). Then the risk variables of bankruptcy will be measured by Altman’s prediction model of bankruptcy (Altman and Hotchkiss, 1995, 2006). The result shows that managerial ability has a positive significant effect on tax aggressiveness. Meanwhile, management compensation has a significant negative effect on tax aggressiveness. Furthermore, the bankruptcy risk has a significant positive effect on tax aggressiveness